2013
DOI: 10.1111/j.1438-8677.2012.00710.x
|View full text |Cite
|
Sign up to set email alerts
|

Emerging concept for the role of photorespiration as an important part of abiotic stress response

Abstract: When plants are exposed to stress, generation of reactive oxygen species (ROS) is often one of the first responses. In order to survive, cells attempt to down-regulate the production of ROS, while at the same time scavenging ROS. Photorespiration is now appreciated as an important part of stress responses in green tissues for preventing ROS accumulation. Photorespiratory reactions can dissipate excess reducing equivalents and energy either directly (using ATP, NAD(P)H and reduced ferredoxin) or indirectly (e.g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
207
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 307 publications
(230 citation statements)
references
References 86 publications
(181 reference statements)
7
207
0
2
Order By: Relevance
“…The finding of several mitochondrial enzymes of photorespiration being highly carbonylated (GDC-T, SHM1, and MTLPD1) combined with the decreased abundance of other photorespiration enzymes (GLDP1 and GLDP2) suggests that this process is at least slowed down in ftsh4 mitochondria (Tables I and II). Since photorespiration is considered to be important to prevent ROS accumulation (Voss et al, 2013), the postulated decreased activity of the GDH/SHMT complex could be an additional cause for oxidative stress in ftsh4. Furthermore, among the proteins carbonylated preferentially in ftsh4 is the manganese superoxide dismutase, a key enzyme for eliminating mitochondrial superoxide radicals (Wang et al, 2010).…”
Section: In Ftsh4 the Defective Oxphos System Is Linked To Enhanced mentioning
confidence: 99%
“…The finding of several mitochondrial enzymes of photorespiration being highly carbonylated (GDC-T, SHM1, and MTLPD1) combined with the decreased abundance of other photorespiration enzymes (GLDP1 and GLDP2) suggests that this process is at least slowed down in ftsh4 mitochondria (Tables I and II). Since photorespiration is considered to be important to prevent ROS accumulation (Voss et al, 2013), the postulated decreased activity of the GDH/SHMT complex could be an additional cause for oxidative stress in ftsh4. Furthermore, among the proteins carbonylated preferentially in ftsh4 is the manganese superoxide dismutase, a key enzyme for eliminating mitochondrial superoxide radicals (Wang et al, 2010).…”
Section: In Ftsh4 the Defective Oxphos System Is Linked To Enhanced mentioning
confidence: 99%
“…In addition, a wheat (Triticum aestivum) stay-green mutant (tasg1) displays delayed chlorophyll turnover and improved tolerance to drought because of the enhanced stability of thylakoid membranes (Tian et al, 2013). The stable chloroplasts also could contribute to maintain photorespiration, which has been shown to increase tolerance to abiotic stress by protecting the photosynthetic apparatus from oxidative damage and optimizing photosynthesis (Rivero et al, 2009;Voss et al, 2013). Here, we showed that silencing of CV increased chloroplast stability and prevented premature senescence under salt, oxidative, and drought stress ( Figure 5; Supplemental Figures 9B and 10).…”
Section: Stress Tolerance Is Increased By Stabilization Of the Chloromentioning
confidence: 99%
“…Therefore, PR metabolism is of vital importance for all oxygenic photosynthetic organisms (Eisenhut et al, 2008;Bauwe et al, 2012), as documented by the observation that cyanobacterial, green algal, and plant mutants in this pathway can only survive in an atmosphere with elevated CO 2 levels (Somerville and Ogren, 1979;Somerville, 2001;Nakamura et al, 2005;Voll et al, 2006;Engel et al, 2007;Schwarte and Bauwe, 2007;Eisenhut et al, 2008;Timm et al, 2011). Besides its metabolic repair function in the removal of the Rubisco's oxygenation product 2PG and carbon salvage, PR metabolism has also been suggested to protect from photoinhibition (Heber and Krause, 1980;Osmond, 1981;Kozaki and Takeba, 1996;Takahashi et al, 2007;Voss et al, 2013). PR is crucial for maintaining the activity of the CBB cycle, since it prevents both the accumulation of enzymeinhibiting metabolites (Anderson, 1971;Kelly and Latzko, 1976;Norman and Colman, 1991) and the depletion of intermediates from the CBB cycle.…”
Section: Introductionmentioning
confidence: 99%